An interventional image‐guided microdevice implantation and retrieval method for in‐vivo drug response assessment. Issue 11 (26th September 2019) - Bhagavatula, Sharath K.; Upadhyaya, Kunj; Miller, Brendyn J.; Bursch, Patrick; Lammers, Alex; Cima, Michael J.; Silverman, Stuart G.; Jonas, Oliver
Abstract : Purpose: Recently developed implantable microdevices can perform multi‐drug response assessment of cancer drugs in‐vivo, with potential to develop highly optimized personalized cancer treatment strategies. However, minimally invasive/interventional image‐guided methods of in‐vivo microdevice implantation, securement, and retrieval are needed for broad clinical translation. Here we demonstrate proof‐of‐concept of an interventional microdevice implantation and retrieval method for personalized drug response assessment, using ex‐vivo phantom, ex‐vivo tissue, and in‐vivo murine models. Methods: A method for minimally‐invasive microdevice implantation and retrieval was developed, by which a custom‐prototyped 6 mm retrievable microdevice can be implanted into a live tumor, deliver drugs into 10 discrete regions of adjacent tissue, and retrieved along with the adjacent drug‐exposed tissue with a custom‐prototyped retrieval needle device to allow in‐vivo multi‐drug response assessment. Computed tomography (CT) and ultrasound (US)‐guided minimally invasive microdevice implantation and retrieval were tested in ex‐vivo phantom and tissue models. Successful retrieval was defined as retrieval of the microdevice and adjacent core phantom/tissue sample containing at least 4/10 drug delivery sites. Subsequently, 10 implantation and retrieval trials in phantom models were performed using bi‐axial and tri‐axial retrieval needles; success rates were calculated and compared using a two‐proportion z ‐test and the number of successfully retrieved drug release sites per microdevice was calculated and compared using a one‐tailed independent t ‐test. Finally, five microdevices, each containing ten reservoirs preloaded with chemotherapy agent Doxorubicin, were implanted into mouse tumors in‐vivo, secured for 24‐h during drug release, and microdevice/tissue retrieval was performed under ultrasound guidance. Fluorescence microscopy of the retrieved tissue was used to confirm drug delivery and apoptosis staining assessed in‐vivo tissue response; correlation of drug release and apoptosis staining were used to assess in‐vivo drug efficacy. Results: Image‐guided microdevice implantation and retrieval were successful in ex‐vivo phantom and tissue models with both US and CT guidance. Bi‐axial retrieval success rate was significantly higher than triaxial retrieval in ex‐vivo phantom trials (90% vs 50%, z  = 1.95, P  = 0.026), and had nonsignificantly higher number of retrieved drug‐release sites per microdevice (8.3 vs 7.0, t  = 1.37, P  = 0.097). Bi‐axial retrieval was successful in all five in‐vivo mouse tumor models, and allowed in‐vivo drug response assessment at up to ten discrete drug delivery sites per microdevice. An average of 6.8/10 discrete tumor sites containing micro‐doses of delivered drug were retrieved per in‐vivo attempt (min 5, max 10, std 1.93). Tissue regions of drug delivery, as assessed with fluorescent Doxorubicin drug signal, correlated with regions of apoptosis staining in all in‐vivo models, indicating drug efficacy. No bleeding, microdevice migration, or other complications were noted during implantation, 24‐h observation, or retrieval. Conclusions: The demonstrated image‐guided minimally invasive microdevice implantation and retrieval method is similar to routine outpatient biopsy procedures, obviates the need for surgery, and can be performed at varying depths under CT and/or US guidance. There is potential for this method to enable clinical translation of in‐vivo personalized drug response assessment/prediction in a much larger number of patients than currently possible.